Update for the Performance of CT Coronary Angiography – Evidence-Based Application and Technical Guidance According to Current Consensus Guidelines and Practical Advice from the Clinical Routine - Soschynski, Martin; Hagar, Muhammad Taha; Taron, Jana; Krauss, Tobias; Ruile, Philipp; Hein, Manuel; Nührenberg, Thomas; Russe, Maximilian Frederik; Bamberg, Fabian; Schlett, Christopher L (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
Background Coronary CT angiography (cCTA) is a class 1 recommendation in the current guidelines by the European Society of Cardiology (ESC) for excluding significant coronary artery stenosis. To achieve optimal image quality at a low radiation dose, the imaging physician may choose different acquisition modes. Therefore, the consensus guidelines by the Society of Cardiovascular Computed Tomography (SCCT) provide helpful guidance for this procedure.Method The article provides practical recommendations for the application and acquisition of cCTA based on the current literature and our own experience.Results and Conclusion According to current ESC guidelines, cCTA is recommended in symptomatic patients with a low or intermediate clinical likelihood for coronary artery disease. We recommend premedication with beta blockers and nitrates prior to CT acquisition under certain conditions even with the latest CT scanner generations. The most current CT scanners offer three possible scan modes for cCTA acquisition. Heart rate is the main factor for selecting the scan mode. Other factors may be coronary calcifications and body mass index (BMI).Key Points: Citation FormatHintergrund Die computertomografische Koronarangiografie (cCTA) hat in den aktuellen Leitlinien der European Society of Cardiology (ESC) einen hohen Stellenwert für den Ausschluss signifikanter Koronarstenosen. Für eine optimale Bildqualität bei niedriger Strahlenexposition stehen dem Untersucher verschiedene Scanverfahren zur Verfügung. Aktuelle Konsensusempfehlungen der Society of Cardiovascular Computed Tomography (SCCT) geben Hinweise für die Durchführung.Methode Der Artikel gibt praktische Empfehlungen zum leitliniengerechten Einsatz und zur Durchführung der cCTA basierend auf der aktuellen Literatur und eigenen Erfahrungswerten.Ergebnisse und Schlussfolgerung Gemäß den aktuellen Leitlinien der ESC wird die cCTA vor allem bei symptomatischen Patienten mit niedriger und intermediärer klinischer Wahrscheinlichkeit für eine koronare Herzkrankheit (KHK) empfohlen. Vor der Untersuchung empfehlen wir selbst an den modernsten Scannern weiterhin eine Prämedikation mit Beta-Blockern und Nitraten. Für die Akquisition stehen an aktuell verwendeten CT-Scannern 3 Scan-Modi zur Verfügung. Hauptfaktor für die Protokollauswahl ist die Herzfrequenz, Nebenfaktoren können Koronarkalk und Body-Mass-Index (BMI) sein.Kernaussagen: Zitierweise
Keywords: coronary CT angiography; acquisition; technique; guidelines; cardiac CT; performance